2014
DOI: 10.1007/s00248-014-0472-8
|View full text |Cite
|
Sign up to set email alerts
|

Amazonian Dark Earth and Plant Species from the Amazon Region Contribute to Shape Rhizosphere Bacterial Communities

Abstract: Amazonian Dark Earths (ADE) or Terra Preta de Índio formed in the past by pre-Columbian populations are highly sustained fertile soils supported by microbial communities that differ from those extant in adjacent soils. These soils are found in the Amazon region and are considered as a model soil when compared to the surrounding and background soils. The aim of this study was to assess the effects of ADE and its surrounding soil on the rhizosphere bacterial communities of two leguminous plant species that frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Biochar is a fine-grained charcoal that is rich in organic carbon, produced by pyrolysis or by heating biomass in a low oxygen environment and has been used worldwide as a soil amendment to increase soil fertility (Lehmann and Joseph, 2009 ; Schomberg et al, 2012 ). However, biochar application is a very old method of improving soil quality and plant growth, as reported by the Amazonian Dark Earths (ADE) or Terra Preta de Índio formed in the past by pre-Columbian populations (Barbosa Lima et al, 2015 ). Presently, there are extensive literature reviews about the use of biochar and hydrochar to mitigate climate change by increasing carbon storage in soils (Lehmann et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar is a fine-grained charcoal that is rich in organic carbon, produced by pyrolysis or by heating biomass in a low oxygen environment and has been used worldwide as a soil amendment to increase soil fertility (Lehmann and Joseph, 2009 ; Schomberg et al, 2012 ). However, biochar application is a very old method of improving soil quality and plant growth, as reported by the Amazonian Dark Earths (ADE) or Terra Preta de Índio formed in the past by pre-Columbian populations (Barbosa Lima et al, 2015 ). Presently, there are extensive literature reviews about the use of biochar and hydrochar to mitigate climate change by increasing carbon storage in soils (Lehmann et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anders et al ( 2013 ) stated that the change in the structure of the microbial community by biochar application is an indirect effect and depends on soil nutrient status. Barbosa Lima et al ( 2015 ) revealed that soil type contributes to the composition of bacterial communities in studies of forest sites ( Mimosa debilis ) and open areas ( Senna alata ) in the Amazon region. However, despite numerous reports on microbial changes induced by biochar application in various cropping systems, there have been no studies on how biochar affects the diversity and physiological activity of plant growth stimulating rhizobacteria, especially in legumes.…”
Section: Introductionmentioning
confidence: 99%
“…The anthropogenic, pre-Columbian soils occur in 20-ha average spots in the Amazonian region [ 2 ]. ADE is recognized by the elevated amounts of stable carbon (70 times more black carbon) and fertility due to the high concentration of P, Ca, Mg, and Zn, nutrient holding capacity, and higher pH when compared to adjacent non-anthropogenic origin soils [ 3 , 4 ]. Despite evidences of human occupation in the Amazon region dating 10,000 years BP (before present), Neves and co-workers [ 5 ] suggested that ADE formation occurred 2500 to 2000 years ago as a result of population increasing during that period.…”
Section: Introductionmentioning
confidence: 99%
“…Significant advances in soil microbial ecology studies were obtained in the last few years after the adoption of high-throughput 16S ribosomal RNA (rRNA) gene sequencing technologies [ 11 ]. This approach was used to investigate the bacterial community associated with biochar samples of ADE [ 12 ] and the effect of ADE and plant species on the selection of rhizosphere bacterial communities [ 4 ]. However, the fungal communities associated with ADE have not yet been investigated with culture-independent methods despite the ecological importance of fungi in terrestrial ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…3). Several studies have been conducted in Caldeirão to investigate ADE characteristics (Barbosa Lima et al, 2015;Germano et al, 2012;Kern et al, 2019;Nakamura et al, 2014;Schellekens et al, 2017;Schmidt, 2006;Schmidt et al, 2014;Taube et al, 2013), which makes it one of the most extensively studied and represented ADE site. Nonetheless, future studies at other ADE sites are encouraged to use the geostatistical method I propose in Chapter 2 (Alho et al, 2019) for a better comprehension of the high spatial variation in other ADE sites and to systematically distinguish ADE from ADJ and therefore account for the overall differences between these areas.…”
Section: Reflections On the Limitations Of This Workmentioning
confidence: 99%